CORRELATION BETWEEN COURSE SCORES AND TUTEP SCORES - Wijaya, Bambang; ., Sudarsono; ., Regina (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2015)
Abstract: This study investigated the correlation between Course Scores and TUTEP scores of the graduates of English Education Study Program, Teacher Training and Education Faculty, Tanjungpura University in Calendar Year 2013. It also investigated the relationship between all related course scores (Listening, Structure, and Reading courses) and the TUTEP section scores (Listening, Structure and Written Expression, and Reading Sections). The sample of 79 students for the study which consisted of 54 Regular A and 25 Regular B students was drawn using cluster random sampling technique. The course scores and the TUTEP scores were analyzed, first, to ensure no violation of correlation procedure, and, second, using Pearson Product Moment Procedures through the use of SPSS Version 17.0 to yield the results of the study.The results of the study showed that there were significant positive linear correlations: between Course Scores and TUTEP Scores (r = 0.589 at 0.01 level); between Structure Course Scores and Structure and Written Expression TUTEP Section Scores (r = 0.323 at 0.01 level); between Reading Course Scores and Reading TUTEP Section Scores (r = 0.266 at 0.05 level); and between Listening Course Scores and Listening TUTEP Section Scores (r = 0.495 at 0.01 level). Keywords: Correlation Study, TOEFL, TUTEP. Abstrak: Penelitian ini tentang korelasi antara nilai mata kuliah dan nilai TUTEP padaÂ Lulusan S-1 Program Studi Bahasa Inggris, Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Tanjungpura (UNTAN) pada tahun kalender 2013. Penelitian ini juga menyangkut hubungan antara semua nilai mata kuliah (Listening, Reading dan Structure) dan nilai TUTEP (Listening, Reading dan Structure and Written Expression). 79 sampel yang terdiri dari 54 Reguler A dan 25 Reguler B diambil dengan teknik cluster random sampling. Nilai mata kuliah dan nilai TUTEP dioleh untuk menentukan pemenuhan syarat korelasi, dan kemudian dianalisa dengan rumus Pearson Prudyct Moment melalui SPSS versi 17.0. Hasil penelitian ini menunjukkan bahwa terdapat korelasi linier positif yang significant: antara total nilai mata kuliah dan total nilai TUTEP (r = 0.589 pada tingkat alpha 0.01); antara nilai mata kuliah structure dan nilai TUTEP bagian Structure and Written Expression (r=0.323 pada tingkat alpha 0.01); antara nilai mata kuliah Reading dan nilai TUTEP bagian Reading (r=0.266 pada tingkat alpha 0.05); dan antara nilai mata kuliah Listening dan nilai TUTEP bagian Listening (r=0.495 pada tingkat alpha 0.01). Kata Kunci: Studi Korelasi, TOEFL, TUTEP.